2010
DOI: 10.3176/oil.2010.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil Shale Ash Application on Leaching Behavior of Arable Soils: An Experimental Study

Abstract: Oil shale ash contains mineral ingredients of agricultural importance and could be used for treatment of soils. However, the ash contains several hazardous ingredients, i.e. toxic trace metals which could be mobile and create environmental concerns. Beneficial use of the oil shale ash in agriculture and forestry requires better knowledge of leaching characteristics of soil-ash systems. In this study two different ash samples have been added to two types of soil, particularly Rendzic Leptosol and Podzolic Gleys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…In the latter case it is important to note that the direct contact of fly ash with soils matrix may considerably decrease the bioavailability of trace metals [48]. Indeed, our test results also showed that even short-term contact of PF-E 1:10 eluates with soil significantly reduced its toxicity to D. magna (data not shown).…”
Section: Biotesting Of Eluatesmentioning
confidence: 69%
“…In the latter case it is important to note that the direct contact of fly ash with soils matrix may considerably decrease the bioavailability of trace metals [48]. Indeed, our test results also showed that even short-term contact of PF-E 1:10 eluates with soil significantly reduced its toxicity to D. magna (data not shown).…”
Section: Biotesting Of Eluatesmentioning
confidence: 69%
“…De acordo com esses autores, a baixa concentração de metais tóxicos no XR propicia o seu uso como condicionador de solos, sem causar riscos. Adamson et al 24 26 são textura arenosa desde a superfície até um mínimo de 50 cm e um máximo de 100 cm de profundidade e horizonte B textural (conteúdo de argila maior em relação ao horizonte A) dentro de 200 cm do perfil do solo.…”
Section: Introductionunclassified
“…Agitated mixtures resulted in slight leaching of these metals in the present case [5]. Leaching conditions are very important [11].…”
Section: Heavy Metals Leachabilitymentioning
confidence: 59%